Molecular modelling: electronic structure methods - Clark, Tim (Henry Stewart Talks, 2011)
Electronic structure theory, The Schrodinger equation, Molecular-orbital theory, Huckel theory, Self-consistent field theory, Neglect of diatomic differential overlap (NDDO), Ab initio theory, Basis sets, Correlation, Density, Functional theory